Determining Mental Health, Psychosocial, and Related Factors among Informal Workers in Bangkok, Thailand - Niranyakarn Chantra; Phassakorn Klinkwan; Saovalug Luksamijarulkul; Amonrat Luenam; Pataraporn Yubonpunt (Universitas Airlangga, 2023)
Introduction: The informal workers in Bangkok have low income, high expenses, and inequity in health coverage, especially in Bangkok metropolitan area. Moreover, the urban lifestyle was severer than in rural area. However, their mental heaths were not directly determined. Therefore, the objective of this study was aimed to determine the relationship among mental health and related factors including demographic data, health behaviors, and coping responses. Methods: The research areas in Bangkok metropolitan area were included voluntarily which were Ladkrabang, Prawet, and Prapradang districts and the subjects were recruited from conventional sampling. They were interviewed by questionnaire. Results: The subjects were 94 male and 76 female informal workers. Most of them finished primary school and an average income was 9,019.68 bahts per month. The happiness score was 31.56 (S.D.=5.06). The mental state was 11.1(S.D.=3.04), mental capacity was 6.25 (S.D.=1.49), mental quality was 6.92(S.D.=1.31) and family support was 7.28 (S.D.=1.41). Conclusion: The happiness and work-family balance were in medium; the others were in high level. The work-family balance, medium work demands, financial status and occupations are the potential factors that affected to mental health status of the informal workers. Discussion: The mental capacity and the work-family balance need to be improved for increasing their mental health status. Hence, the working schedule should be arranged and the monitoring of mental health status should be monitored in further study.